Design of Disaster Mitigation E-Booklet for Tourists (Case Study of Marine Tourism on the West and East Pangandaran) - Deis maryani Deis (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: Analyzing mitigation strategies that can be implemented to optimize the tourist experience while preserving the local environment and culture. Method: Using a qualitative approach, data were collected through interviews with relevant stakeholders, field observations, and document studies. Result: The analysis results indicate that several effective mitigation measures include regulating the number of visitors, environmental education, developing eco-friendly infrastructure, and enhancing local community involvement in tourism management. By implementing appropriate mitigation strategies, Pangandaran is expected to maintain its appeal as a tourist destination while preserving environmental sustainability and cultural heritage. Contribution: This study provides recommendations for tourism managers and local governments in formulating more effective policies and actions to address the challenges of tourism in the modern era.